Two hospitals by architect Chorão Ramalho: considerations on the valorization of their artistic heritage - Mehnert Pascoal, Ana (2019)
This text proposes a brief reflection on the heritage value of hospital buildings planned during the final decade of the Estado Novo regime in Portugal (1933-1974). It focuses on the implementation of a hospitalnetwork constructed by the Hospital Construction Committee (later Directorate General of Hospital Buildings), under the Ministry of Public Works, and the reorganization of the country’s health and assistanceservices. Two hospitals designed by architect Raúl Chorão Ramalho (1914-2002) are discussed: Hospital José Joaquim Fernandes (1970/1976-1981) in Beja and Hospital de Santa Luzia (1984) in Viana do Castelo, which are permanently functioning since their inauguration. Further considerations will be made on their preservation and valorisation, as well as on the heritage dimension enhanced by their art works.